2018
DOI: 10.1002/ijc.31390
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type specific risk of progression and remission during long‐term follow‐up of equivocal and low‐grade HPV‐positive cervical smears

Abstract: The prevalence of clinically relevant HPV types and their specific risk for progression and regression in women with atypical squamous cells of uncertain significance (ASCUS) and low-grade squamous intraepithelial lesions (LSIL) were studied in a routine screening population. A 4-year cohort of women (n = 820) with ASCUS/LSIL and a positive HPV test in triage were followed for 6-9 years. The progression risks for CIN2+/CIN3+ were determined for single (71.2%) and multiple HPV infections (28.8%). The CIN2+ prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The virus can be cleared through host immune responses spontaneously, only a small number of infections persisted and progressed to cervical cancer [36]. HPV 16 was found to be the most prevalent hr-HPV type with the highest risk among all hr-HPVs to progress to CIN2-3 and ICC [37]. Studies found that the outcome of HPV infection was closely related to the local micro-environmental of the cervix [27].…”
Section: Discussionmentioning
confidence: 99%
“…The virus can be cleared through host immune responses spontaneously, only a small number of infections persisted and progressed to cervical cancer [36]. HPV 16 was found to be the most prevalent hr-HPV type with the highest risk among all hr-HPVs to progress to CIN2-3 and ICC [37]. Studies found that the outcome of HPV infection was closely related to the local micro-environmental of the cervix [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that presence of HPV-16 is a major factor for risk of CIN grade 3 or higher. 30,31 A 2016 cohort study 31 found that HPV-16 and HPV-18 are associated with the greatest 3-year risk of CIN grade 3 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…40 This measurement error could be higher in the group of women whose results were negative in HPV-16/HPV-18 genotyping and normal in LBC who were used for VBA, considering that CIN grade 2 lesions caused by high-risk HPV types other than HPV-16 or HPV-18 are more likely to regress. 30,32,41,42 A 2016 study 31 indicated that the 3-year risk of CIN grade 3 or higher ranged from 1.2% to 4.0% for patients with high-risk HPV who did not have HPV-16 or HPV-18 and had normal cytological findings. This can lead to an underestimation of the true sensitivity and specificity of the analysis if using VBA.…”
Section: Discussionmentioning
confidence: 99%
“…Certain strains of the HPV are known to be the primary causes of cervical cancer, and certain conditions accelerate progression from low-grade lesions caused by HPV to cancer. [32][33][34][35] Exposure to HPV is typically through sexual contact, thus risk of HPV infection is highly correlated with age. Moreover, the dependence on age is nonmonotonic, as the exposure to HPV increases from late teens to mid-twenties and then decreases as women get older, with a possible slight increase in risk in early middle-age.…”
Section: Markov Model For Cervical Cancermentioning
confidence: 99%